LEARNING ORGANIZATION LEADERSHIP INNOVATION (LOLI) AND EMPLOYEE PERFORMANCE IN CREATIVE INDUSTRIES - Titiek Ambarwati; Fika Fitriasari; Ratya Shafira Arifiani (Manajemen Bisnis, 2020)
This study aims to analyze the direct influence of leadership on learning organization, the influence of learning organization on employee performance, the influence of leadership on innovation, and the influence of innovation on employee performance. The population in this study was all employees of handicraft Small and Medium Enterprises (SME) in Malang City. The sampling technique used is probability sampling with a sample size of 50 respondents. The analysis used is path analysis using SmartPLS 3.0 software. The results showed that leadership has an influence on the application of learning organization, learning organization has an effect on employee performance, leadership encourages employees to innovate, and the innovations can improve employee performance. The role of a leader to encourage employees to continue learning and innovating in SMEs will create a good impact on the performance of employees and SMEs.